(untitled) (Revista Apotheke, 2022)
This article consists of the investigations that have been carried out in the Completion Work of the Degree Course in Visual Arts at the Federal University of Amapá. The research is focused on the language of performance, investigating how this artistic practice resonates with questions about the decolonization of bodies and knowledge produced in the Amazon region. In the first moment of the research was created a mini-course for students of the Degree in Visual Arts at the institution itself, whose methodology is cartography. Initially, it was possible to glimpse that there is a great interest on the part of students in undertaking investigations about their ancestral knowledge, as well as, proved to be emerging to a dissident art education.